Monuments Without Faces? - Shelby Green (Washington University Journal of Law and Policy, 2023)
Monuments take many forms and can serve several purposes. Typically associated with honor and a need to commemorate significant events, monuments seem to represent the ideas of the communities which house them. However, it remains to be seen whether all monuments represent a “good” memory. In this essay, the author seeks to comment on the concept of collective memory, specifically in the context of the history and experiences of marginalized groups in the United States. The author argues that monuments are a tool of promoting a collective memory: monuments are not part of history but rather part of the creation of a particular narrative of the past. Protecting monuments from removal allows these memorials to remain prominent influences in the public spaces they inhabit – perpetuating their influence on the collective memory. The author considers whether any, some, or all Confederate monuments should be removed and the implications of such removals. Moreover, the paper explores different responses which may be pursued in response to the preservation of Confederate monuments with a focus on counter-narratives. Ultimately, the author advocates for a move away from monuments which promote a collective memory in favor of monuments which encourage questions and discourse.
Keywords: Monuemnts; Memory; Removal; Confederate; Discourse; Collective Memory